Working Group on Bycatch of Protected Species (WGBYC) ... - ICES (ICES Scientific Reports, 2024)
Note: Risk score Table 6.1 can be downloaded. January 2024: Report updated with the correct list of WGBYC 2023 meeting participants (in Annex 1) October 2024 (minor edits): Risk table 6.1 corrected to ToR E. The Working Group on Bycatch of Protected Species (WGBYC) was established in 2007 and collates and analyses information from across the Northeast Atlantic and adjacent sea areas (Baltic, Mediterranean and Black Seas) related to the bycatch of protected, endangered and threatened (PET) species, including marine mammals, seabirds, turtles and sensitive fish species in com-mercial fishing operations.WGBYC seeks to describe and improve understanding of the likely impacts of fishing activities on affected populations, to inform on the suitability of existing at-sea monitoring programmes for assessing sensitive species bycatch, and to collate information on bycatch mitigation efforts. In 2023, the WG met in hybrid format and addressed eight Terms of Reference.The report provides an overview of data collection ...